Using SMS as a tool to reduce exclusions experienced by caregivers of people with disabilities in a resource-limited Colombian community (2015)
Purpose: The community of El Codito, located in the mountainside on the perimeter of Bogota, Colombia, is considered one of the most vulnerable and resource-limited communities in the region. This community-based research (CBR) project used short message service (SMS) messaging as a tool for information access and social interaction with caregivers of people with disabilities (PWD). Method: Using a focused ethnographic method, this research evaluated the experience of caregivers participating in the project. In addition to primarily qualitative methods, supplementary quantitative message data was also collected. This project utilized free and open source software for SMS message distribution. Results: Caregivers experienced the project as a window to possibility; the possibility of a social support network, the possibility of community participation and the possibility of change. During the three-month implementation, a total of 56 information messages were sent to caregivers, 20 question messages were received from caregivers and 30 social interaction messages were sent by caregivers to the group. Conclusions: The proliferation of mobile phones in this resource-limited setting provided a feasible method for reducing the exclusion of PWD and caregivers. SMS was a useful tool for sharing information and reducing the isolation experienced by this socially excluded population. © 2014 Informa UK Ltd.